In Situ Probing of Surface Acoustic Waves by Interfacing with Lanthanide Emitters. Issue 3 (27th November 2020) - Zhao, Yanan; Yuan, Yang; Chen, Haisheng; Chen, Wenwen; Du, Xiaona; Gong, Cheng; Lin, Lie; Luo, Wei; Liu, Weiwei; Zhang, Yang
Abstract: Surface acoustic waves (SAWs) are used in a broad range including electronic systems and various sensors. Especially, SAW‐based microfluidic actuations at microscale represent an effective way with unrivaled precision and technological relevance. However, it remains a daunting challenge to develop a reliable and robust method for in situ and real time probing of the acoustic propagation of SAWs. Approach‐based sophisticated equipment claims large consumption and fussy operation, and is also limited for rapid analysis inside microfluidic channels. Other emerging methods suffer from limitations associated with the reproducibility or the application scenarios. Here, a convenient approach is achieved by interfacing with lanthanide emitters. The coupling between ferroelectric host and lanthanide ions promises effective emission manipulation upon external stimuli induced by the SAWs. The photoluminescence fluctuations of lanthanide emitters reflect their interaction with the strain and piezoelectric fields accompanying the propagating SAWs. The strong correlation between the lanthanide luminescence and the acoustic fields can visualize the resonant frequency, energy flow as well as propagation loss of the propagating SAWs on demand without degrading the SAW‐based functionality. These findings would accelerate the development of SAW‐based devices owing to the added functionality provided by the SAW‐luminescence correlative character. Abstract : A convenient and visible method for in situ probing of surface acoustic waves (SAWs) is proposed by interfacing lanthanide emitters. The correlation between the lanthanide luminescence and the acoustic fields can deliver the information of resonant frequency, energy flow, and propagation loss from the SAWs. The convergence of SAWs with lanthanide luminescence would promote the innovation of SAW‐based microfluidic devices.